UN COVID 19 Disability Inclusion Strategy: Assessing the Impact on Cultural-Safety and Capability Information Approach - Nwachukwu, P.T.T.; Asuelime, L. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
This paper is aimed at exploring the role of the United Nations Disability Inclusion Strategy as a rights-based concept in understanding the recent COVID-19 outbreak; and how Cultural-Safety Capability Information, visible within the DSM-5, is linked with the achievable recovery and inclusion for persons with disabilities and post-COVID-19 pandemic for health and social care practitioners. There are two measured, actionable targets from the Disability Inclusion Strategy that are geared towards achievable standards of health for persons with disabilities, which are the identifying and eliminating of obstacles and barriers to accessibility in healthcare facilities and the training of healthcare personnel on disability inclusion and improving service delivery for persons with disabilities. The concepts of recovery and inclusion are discussed within a rights-based, and Cultural-Safety Capability Information (DSM-5) approaches in order to curb the COVID-19 info-demic (Information epidemic). This paper has recommendations for the United Nations Disability Inclusion Strategy as a rights-based idea and the re-educating and re-orientation of both the right-holders, persons with disabilities, for example, and the duty-bearers. This paper also discusses the health and social care practitioners and their realisation of health care and recovery, curbing inequalities in accessing health care, education, and easing participation for persons with disabilities during the COVID-19 pandemic